From «апостол» to «аутодафе»: a fragment of the «encyclopaedic dictionary of christian words in russian» - Dobrushina Ekaterina (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The publication presents the third part of entries beginning in the letter «A», the fragment of the dictionary of Christian words in Russian, which is being compiled by staff members of the Department of Philology and the Department of Theology of St. Tikhon’s Orthodox University for the Humanities. The introductory article setting out the main principles of the work was published in Issue 3 (25), 2011, the second part of entries in Issue 2 (28), 2012.